An efficient construction of CN bond under catalyst‐free and room temperature conditions. (14th March 2021) - Zhang, Jinpeng; Liu, Jing; Dai, Lei; Ge, Yuqian; Xu, Linlin; Xia, Yingying; Xu, Lan; Rong, Liangce
Abstract: An efficient and facile process for the construction of CN bond from 1, 6‐conjugate addition reaction of 4‐arylidene‐2, 6‐di‐tert‐butylcyclohexa‐2, 5‐dien‐1‐one (or substituted 3‐[3, 5‐di‐tert‐butyl‐4‐oxocyclohexa‐2, 5‐dien‐1‐ylidene]indolin‐2‐one) and substituted 1, 2, 3, 4‐tetrahydroisoquinoline (or substituted indoline) at room temperature was reported. The advantages of this reaction were catalyst‐free, mild condition, broad substrate scope, and environmentally benign process. Abstract :